2018
DOI: 10.21614/chirurgia.113.4.576
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Diverticulitis Mimicking Small Bowel Perforation: Case Report and Review of the Literature

Abstract: Jejunal diverticulitis is a rare entity with a higher prevalence among patients between 60 and 70 years. Jejunal diverticula are most often considered an incidental finding, but, they can have complications such as diverticulitis, perforation, abscess, generalized peritonitis, fistula, obstruction and bleeding.Setting the diagnosis still remains challenging. Physicians should be aware of their existence and the clinical suspicion should be raised, especially in the setting of acute abdominal pain where jejunal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…When the perforation causes localized peritonitis but the patient has stable vital signs, conservative treatment with a percutaneous Ct-guided aspiration of the intraperitoneal collection can be performed with good results, avoiding the need of surgery [12,14]. Lesser procedures as diverticulectomy, simple closure or invagination of the diverticulum are associated with a three time higher mortality rate [10,12,14] and are only recommended when the perforated diverticulum is situated next to the duodeno-jejunal flexure, because of difficulties in managing anastomotic complications at this region [14]. However, the treatment of choice for complicated jejuno-ileal diverticulitis causing generalized peritonitis is prompt laparotomy with segmental small bowel resection followed by primary anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the perforation causes localized peritonitis but the patient has stable vital signs, conservative treatment with a percutaneous Ct-guided aspiration of the intraperitoneal collection can be performed with good results, avoiding the need of surgery [12,14]. Lesser procedures as diverticulectomy, simple closure or invagination of the diverticulum are associated with a three time higher mortality rate [10,12,14] and are only recommended when the perforated diverticulum is situated next to the duodeno-jejunal flexure, because of difficulties in managing anastomotic complications at this region [14]. However, the treatment of choice for complicated jejuno-ileal diverticulitis causing generalized peritonitis is prompt laparotomy with segmental small bowel resection followed by primary anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the treatment of choice for complicated jejuno-ileal diverticulitis causing generalized peritonitis is prompt laparotomy with segmental small bowel resection followed by primary anastomosis. This is especially recommended when bleeding, obstruction or signs of perforations are shown [10,[12], [13], [14]]. As a matter of fact, Wilcox and Clayton in 1988 stated that retrospective studies showed that up to 15% of patients with jejunal diverticulosis will require intestine resection for complications such as perforation and diverticulitis [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of small bowel diverticulitis is small; prevalence increases with age, characteristically in males in the sixth to eighth decades of life [3, 4]. Jejunal diverticula are thought to be pulsion diverticula secondary to intestinal dyskinesia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Jejunal diverticula are thought to be pulsion diverticula secondary to intestinal dyskinesia [3]. Although jejunal diverticula are not an unusual finding within themselves, they create a nidus for possible complications including perforation, bleeding, abscess and obstruction [4]. The effects of these possible outcomes may lead to clinically confusing presentations, such as iron deficiency anemia due to diverticular bleeding [5].…”
Section: Introductionmentioning
confidence: 99%